Ecological Leadership of Kiai M. Faizi - HS, Dedi Eko Riyadi; Zuhri, Achmad Muhibbin; Salik, Mohamad (Journal of Pesantren and Diniyah Studies, 2024)
This study aims to describe ecological leadership as a form of leadership of Kiai M. Faizi, who is concerned about environmental cleanliness, which is implemented in managing a waste-free Islamic boarding school, especially plastic waste. This study was conducted at the Annuqayah Islamic Boarding School in the Sawajarin area, using a qualitative approach with a phenomenological type. Data collection used a structured interview method with the caretaker, in-depth observation of ecological plastic waste-free practices, and documentation. The analysis method used the Moustakas structured pattern: 1) description of phenomena, 2) horizonalization, 3) cluster of meaning, and 4) essence description. The study results showed that M. Faizi's leadership in forming the ecological piety of students used two steps, namely, revitalization of religious teachings and role models and changing the slogan "put trash in its place, not to trash." The ecological leadership pattern applied has an impact in the form of an attitude of caring for the environment, a clean and healthy lifestyle, a comfortable Islamic boarding school environment, and free from trash, mainly plastic waste.